Women Migrant Workers in Fiqh Perspectives - Lutfiyah, L.; Kistanto, Nurdien Harry; Akmaluddin, Muhammad (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
The purpose of this study is to find information about the law of a wife to be a migrant worker from the perspective of fiqh. This study is qualitative research using library research and uses the fiqh approach. Data sources come from primary and secondary sources. The primary source functions as the main source, obtained by tracing the book of jurisprudence by analyzing the content (content analysis). Secondary sources function to support primary sources obtained through books, journals, and other important documents. The result is that the husband must rethink to permit wives who want to become migrant workers. Changes in Islamic law against migrant workers can occur if they meet the requirements including time, place, intention, and custom. The proof of sadd al-dhari'ah serves to inhibit the rate of sending women migrant workers.